2019
DOI: 10.21873/invivo.11676
|View full text |Cite
|
Sign up to set email alerts
|

Isovitexin Increases Stem Cell Properties and Protects Against PM2.5 in Keratinocytes

Abstract: Background/Aim: Fine airborne particles of Particular Matter of less than 2.5 micrometers (PM 2.5) have been recognized as a dominant air contamination causing critical health concerns. Herein, we determined whether isovitexin, a natural plant-derived compound could protect PM 2.5-mediated oxidative stress and induce stemness in epidermal cells. Materials and Methods: Cell viability was detected by the 3-(4,5dimethylthiazol-2-yl)-2,5 diphenyltetrazolium bromide (MTT) assay. Reactive oxygen species (ROS) were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…The toxicity of vitexin and its derivatives have been observed by (1) studies in vitro using cells or cell lines and (2) in vivo experimentation in animal models. The cytotoxicity of vitexin and isovitexin has been assessed in human leukemia CCRF-CEM cells [ 206 ], macrophages cells (RAW264.7) [ 134 , 207 ], T lymphocytes and RBL-2H3-mast cells [ 99 ], N9 microglial cells [ 74 ], neutrophils [ 106 ], breast carcinoma cell lines, either T47D or MCF-7 [ 203 ], MCF-7, A549, HepG2, and HT-29 cells [ 208 ], HepG2 cells [ 209 ], J774 macrophages cells [ 139 ], and human keratinocyte (HaCaT) cells [ 144 ], and they only exerted negligible to no cytotoxic effects. In addition, vitexin-2″-O-rhamnoside and vitexin-4″-O-glucoside caused no cytotoxic effect on human adipose-derived stem cells, A2780 and MCF-7cells [ 210 , 211 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The toxicity of vitexin and its derivatives have been observed by (1) studies in vitro using cells or cell lines and (2) in vivo experimentation in animal models. The cytotoxicity of vitexin and isovitexin has been assessed in human leukemia CCRF-CEM cells [ 206 ], macrophages cells (RAW264.7) [ 134 , 207 ], T lymphocytes and RBL-2H3-mast cells [ 99 ], N9 microglial cells [ 74 ], neutrophils [ 106 ], breast carcinoma cell lines, either T47D or MCF-7 [ 203 ], MCF-7, A549, HepG2, and HT-29 cells [ 208 ], HepG2 cells [ 209 ], J774 macrophages cells [ 139 ], and human keratinocyte (HaCaT) cells [ 144 ], and they only exerted negligible to no cytotoxic effects. In addition, vitexin-2″-O-rhamnoside and vitexin-4″-O-glucoside caused no cytotoxic effect on human adipose-derived stem cells, A2780 and MCF-7cells [ 210 , 211 ].…”
Section: Resultsmentioning
confidence: 99%
“…Vitexin and isovitexin DPPH radical scavenging activity is suggested to be attributed to the phenolic hydroxyl group in the 4′ position on the B-ring [33,38,143,146,[148][149][150][151][152][153][154][155][156][157]. Moreover, isovitexin-6″-O-α-L-glucoside, vitexin, vitexin-2″-Orhamnoside, and isovitexin demonstrated moderate to high affinity to generated free ABTS•+ in the ABTS assay [44,[141][142][143][144][145][156][157][158][159][160][161][162]. In superoxide radical-scavenging assay, isovitexin and vitexin showed a protective effect against the oxidative-induced reactions by scavenging generated free superoxide anion radicals [37,133,147,150,156,163,164].…”
Section: Reactive Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Niacinamide, a compound that is often used in various cosmetics, was shown to protect keratinocytes from PMinduced oxidative stress [184]. Other reducing agents found to protect the skin against PM are 3,4-dicaffeoylquinic acid [186], 7,3′,4′-trihydroxyisoflavone cyclodextrin inclusion complex [142], isovitexin [176], ginsenoside Rb1 [175], chitosan [259], and SIG-1273, a isoprenylcysteine small molecule [228].…”
Section: Protective Solutions Against Pm-induced Skin Damagementioning
confidence: 99%
“…Over recent years, researchers have attempted to prevent and control the cellular and organ damage caused by PM2.5. Some researchers have shown that some natural compounds, and traditional Chinese medicines, can protect the cell and organ damage induced by PM2.5 both in vitro and in vivo, including isovitexin [21], astaxanthin [22], curcumin [23], astragalus [24], codonopsis pilosula [24], ophiopogonin [25], triptolide [26], astragaloside IV [27], resveratrol [28], and lentinan [29]. All of these studies were carried out in vivo; drugs were administered systematically, by either oral or injection routes.…”
Section: Discussionmentioning
confidence: 99%